1982
DOI: 10.1007/bf00379209
|View full text |Cite
|
Sign up to set email alerts
|

The use of decalcified granulated homologous cortical bone matrix in the correction of diaphyseal bone defect

Abstract: In order to investigate an alternative way to correct diaphysial bone defects, granulated decalcified homologous cortical bone was used as a graft. Because of the suitable anatomic arrangement, the forearm of rabbits was chosen as an experimental model of bone defect. A 2 cm long bone cylinder was removed from the diaphysis of both radii preserving the periosteum. The artificial bone defect was filled with granular decalcified bone on the right side. The left side was used as control and kept empty or filled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…cated use of other materials with osteoinductive properties, such as demineralized bone matrix (1,7,9,10,14,(17)(18)(19)22,23,25,27,28).…”
mentioning
confidence: 99%
“…cated use of other materials with osteoinductive properties, such as demineralized bone matrix (1,7,9,10,14,(17)(18)(19)22,23,25,27,28).…”
mentioning
confidence: 99%
“…Some authors have been conducting experiments in an attempt to isolate substances produced on bodies, which would supposedly be correlated to bone formation. [8][9][10][11][12][13][14]22 In this experiment, three groups of animals were used: group A, submitted to ostectomy and to bone marrow remote stimulation by ablation, in order to assess the systemic osteogenic response after an intensive bone marrow regeneration process; group B, submitted to ostectomy and to bone marrow remote stimulation by placing a Kirschner wire inside the bone marrow in order to assess the systemic osteogenic response after an intensive bone marrow regeneration process , and; group C -control group -which was used for comparison. On the three groups, we performed blood depletion and used a garrote on the operated limb with an elastic band in order to reduce bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous publications in which the authors have addressed the osteogenic capacity of various skeletal tissues and their combinations, or specially treated tissue derivatives (Burwell 1966 Lindholm et al 1982, Volpon et al 1982, Gupta & Tuli 1982, Cummine et al 1983, Wittbjer et al 1983. McDavid et al (1979) found that porous ceramic implants impregnated with bone mattow had bone formation within the pores.…”
Section: Discussionmentioning
confidence: 99%